Gereformeerde teologie in die spervuur tussen fundamentalisme en anti-fundamentalisme - Jordaan, G. J. C. (Acta Theologica, 2004)
Reformed theology is often accused of harbouring fundamentalistic ideas, especially in its views regarding the authority and infallibility of Scripture, the validity of science, the nature of history and philosophical views on truth and reality. However, if compared to the reformed confessional writings, the ideas to which reformed theology subscribe, prove to be rooted in the reformed confession rather than in the concepts of fundamentalism. Although the reformed theology share a number of views with fundamentalism, there are equally a number of matters in which it differs from fundamentalism. Therefore the anti-fundamentalistic accusation against reformed theology proves to be mostly without a sound basis.